Studio 666 [videorecording (DVD)] - Mendel, Nate, 1968-; Smear, Pat; Hawkins, Taylor, 1972-2022; Shiflett, Chris, 1971-; Jaffee, Rami, 1969-; Cummings, Whitney, 1982-; Grossman, Leslie, 1947-; Forte, Will; Ortega, Jenna; Garlin, Jeff, 1962-; Dallatorre, Michael, 1979- (Universal Studios, 2022)
Members of the rock band Foo Fighters move into an Encino mansion steeped in grisly rock n' roll history to record their much-anticipated tenth album.